Letter to members of the Iowa Ornithologists' Union regarding annual meeting, April 1, 1926 - Rosene, Walter, 1880-1941et al; Iowa Ornithologists' Unionet al (1926)
Letter to members of the Iowa Ornithologists' Union giving the dates of May 14-15 for the annual meeting. The letter includes members suggestions for naming a state bird of Iowa. It also has a "Bird Notes" section for bird sighting reports by members. Contex - flatbed